Chronic Lymphocytic Leukemia and Myelofibrosis - Fares Darawshy; Arieh Ben-Yehuda; Karine Atlan; Deborah Rund (Case Reports in Hematology)
Background. Chronic lymphocytic lymphoma (CLL) can be associated with several malignancies, but rarely with myelofibrosis. Only isolated case reports in the literature described the association between CLL and primary myelofibrosis (PMF) in the same patient. Objectives. We describe a case of CLL characterized by the development of PMF and a review of literature. Methods. We describe an 86-year-old female diagnosed as having CLL and followed by the development of splenomegaly and progressively rising LDH levels 27 months later. A bone marrow biopsy was consistent with the diagnosis of PMF, with positive JAK-2 V617F mutation. We also review the clinical and molecular characteristics of patients with CLL and PMF. Results. Patients with CLL and PMF are usually older. A lead diagnosis of CLL harbored by PMF is the most common clinical course, although concomitant diseases may occur in 31.7% of patients. JAK-2 V617F mutation can be found in 48.7% of patients. Conclusion. This case reported here constitutes an unusual situation of CLL characterized by the development of PMF. Etiologic and pathogenic associations—the role of t (1; 6) and JAK-2 V617F mutation—are discussed.